Il messaggio missionario della Radio Vaticana di fronte ai cambiamenti nei media della Santa Sede - Gęsiak, Leszek (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The process of restructuring the Vatican media has continued for several years. The Secretariat for Communication has initiated changes in the structures and programs of all media entities that have operated in the Vatican. The reform radically changes the media strategy of the Holy See. One of the challenges is the missionary function of the Vatican media, so far carried out by Vatican Radio in a very effective way. A brief presentation of the reform shows the ideas guiding this transformation. The most important factor is the openness of today’s world to the Internet and social media. However, it seems that new technologies are not always fully suitable for the “missionary world”, especially in many places in Africa. For this reason it seems important to find a new efficient way of proceeding. Retaining these, Vatican Radio should continue to be a very significant factor in the missionary activities of the Church.